2012
DOI: 10.1021/cm302312a
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating the Morphology of P3HT–PCBM Bulk Heterojunction Blends with Solvent Vapor Annealing

Abstract: Using grazing incidence X-ray scattering, we observe the effects of solvent vapors upon the morphology of poly(3-hexylthiophene)−phenyl-C 61 -butyric acid methyl ester (P3HT−PCBM) bulk heterojunction thin film blends in real time; allowing us to observe morphological rearrangements that occur during this process as a function of solvent. We detail the swelling of the P3HT crystallites upon the introduction of solvent and the resulting changes in the P3HT crystallite morphology. We also demonstrate the ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
218
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 176 publications
(227 citation statements)
references
References 50 publications
9
218
0
Order By: Relevance
“…A P3HT:PCBM film prepared using dichlorobenzene (DCB) [boiling point (bp) = 178 °C] or chlorobenzene (CB) (bp = 132 °C) possesses a better-ordered structure and an improved crystallinity in comparison with a film prepared using the low-boiling solvent, chloroform (CF) (bp = 61 °C), as is shown (Figure 4) by their X-ray diffraction (XRD) intensities [81]. Recently, Verploegen et al [70] studied the differences between the spin-cast films produced with CF or CB as solvents using grazing incidence wide-angle X-ray scattering (GIWAXS) of the film ( Figure 5). They observed that the direction of the P3HT lamellae for the film cast using CB was different from the direction of the P3HT lamellae for the film cast using CF.…”
Section: Roles Of Solvent In Controlling the Active-layer Morphologiesmentioning
confidence: 99%
See 4 more Smart Citations
“…A P3HT:PCBM film prepared using dichlorobenzene (DCB) [boiling point (bp) = 178 °C] or chlorobenzene (CB) (bp = 132 °C) possesses a better-ordered structure and an improved crystallinity in comparison with a film prepared using the low-boiling solvent, chloroform (CF) (bp = 61 °C), as is shown (Figure 4) by their X-ray diffraction (XRD) intensities [81]. Recently, Verploegen et al [70] studied the differences between the spin-cast films produced with CF or CB as solvents using grazing incidence wide-angle X-ray scattering (GIWAXS) of the film ( Figure 5). They observed that the direction of the P3HT lamellae for the film cast using CB was different from the direction of the P3HT lamellae for the film cast using CF.…”
Section: Roles Of Solvent In Controlling the Active-layer Morphologiesmentioning
confidence: 99%
“…A previous result by Moon et al [85] showed a different role played by the CN additive on the morphology of a thin film consisting of (4,4-didodecyldithieno[3,2-b:20,30-d]silole)-2,6-diyl-alt-(2,1,3-benzothiadiazole)-4,7-diyl (Si-PDTBT) donor and [6,6]-phenyl-C 70 -butyric acid methyl ester (PC 70 BM) acceptor. The additive suppressed the large-scale aggregation of PC 70 BM and promoted the correct morphology for high-performance BHJ devices [85]. The nanomorphology of the Si-PDTBT:PC 70 BM BHJ material without the use of a CN additive was indicative of oval-shaped PC 70 BM aggregate with a diameter >200 nm [85].…”
Section: Use Of Chemical Additivesmentioning
confidence: 99%
See 3 more Smart Citations